Chapter In gesprek met Iris Kensmil - Kensmil, Iris (Amsterdam University Press, 2023)
This article is focused on Professor Buikema's intellectual oeuvre and the relation between art and politics as it materialised in MOED (Museum of Equality and Difference). Astrid Kerchman and Rosa Wevers, MOED's former project coordinators, reflect on their collaboration with Buikema through an interview with artist Iris Kensmil on the important role of art in complex social issues relating to emancipation, representation, and resistance. Drawing on the interview with Kensmil and Buikema's Revolts in Cultural Critique (2020), Alessandra Benedicty-Kokken reflects on the meaning of feminist leadership within an institutional context.